How Much Do They Know? Determination of Knowledge about Harmful Effects of Smoking and Alcohol Use in University Students and the Predictors of Substance Use: A Cross-Sectional Study - Hatice Kübra Barcın Güzeldere; Gülin Öztürk Özkan; Berna Dincer (Addicta: The Turkish Journal on Addictions)
Smoking and alcohol consumption have a significant share in the occurrence of chronic diseases, especially cardiovascular heart disease. This study aims to evaluate university students’ level of knowledge on the harmful effects of smoking and alcohol use on health and determine the predictors of smoking and alcohol use. A total of 912 university students, from faculties of health sciences (n = 444) and other faculties (n = 468), participated in the study. The questionnaire consists of three parts and 44 questions. It was deter- mined that students at the Faculty of Health had lower smoking rates (14.4%) and alcohol use (15.8%) than others. The idea that alcohol use is beneficial for health is more common among students of techni- cal and social sciences faculties (26.7%). It was found that Health Sciences and Medical students had a higher level of knowledge of the effects of smoking and alcohol use on health. Besides, the predictors of smoking and alcohol use were determined as department, alcohol use/smoking in their family, intention to quit smoking, and thinking alcohol is beneficial for health. It might be one of the reasons for university students’ smoking and alcohol use is inadequate knowledge about the harmful effects of these substances, including courses on the detrimental impact of smoking and alcohol use in the curriculum can be benefi- cial for improving knowledge and might help reduce the risk of chronic diseases. Public health strategies should be planned for both families and students, and it should be target increase knowledge about harm- ful effects of smoking.